Impact of Wearing Palatal Expanders on the Quality of Life of Children Aged 8 to 10 Years - Milene Torres Martins; Virgínia de Melo Vitorino; Luciana Villela Rodrigues; Elizabeth Maria Bastos Lages; Henrique Pretti; Míriam Parreira Vale; Saul Martins Paiva; Isabela Almeida Pordeus (Association of Support to Oral Health Research (APESB), 2021)
Objective: To assess the impact of wearing palatal expanders on the oral health-related quality of life (OHRQoL) of children aged 8 to 10 years. Material and Methods: The sample consisted of 35 children aged 8 to 10 years treated at the orthodontics and pediatric dentistry outpatient clinics affiliated with the Dental School. Children were divided in two groups: 17 were submitted to palatal expansion treatment (Group 1), while 18 just received coronal polishing and topical fluoride application (Group 2). The Brazilian version of the Child Perceptions Questionnaire (CPQ8-10) was used to assess children's OHRQoL. The questionnaire was administered before the expander was placed, at the end of its activation, and before its removal. Intervals between the interviews were similar in the two groups. Descriptive statistics and ANOVA were used for data analyses. Results: The overall CPQ8-10 score was not significantly different between the groups. The results show statistically significant differences between the two groups only for the functional limitations domain after activation of the appliance (p=0.001). Conclusion: Palatal expanders may negatively affect children's functions only during the initial wearing period.